Cucurbitacin IIa Alleviates Colitis via Promoting the Release of Host-Derived Extracellular Vesicles Encapsulating microRNA-30b-5p - Zhao Y; Jiang B; Zuo S (Journal of Inflammation Research)
Yinyin Zhao,1 Binyuan Jiang,2 Shengnan Zuo3 1Ningbo Institute of Innovation for Combined Medicine and Engineering (NIIME), The Affiliated LiHuiLi Hospital of Ningbo University, Ningbo, People’s Republic of China; 2Medical Research Center of the Affiliated Changsha Central Hospital of Hengyang Medical School, University of South China, Changsha, People’s Republic of China; 3Clinical Laboratory Department, Hunan Guangxiu Hospital, Changsha, People’s Republic of ChinaCorrespondence: Binyuan Jiang; Shengnan Zuo, Email 2018050871@usc.edu.cn; shengnanzuo123@sina.comPurpose: Cucurbitacins have demonstrated anti-inflammatory effects and show promise for inflammatory bowel diseases. However, the underlying mechanisms by which cucurbitacins affect colitis remain largely unknown.Methods: In this study, we investigated the impact of cucurbitacin IIa on dextran sulfate sodium (DSS)-induced colitis in rats and the alterations in intestinal extracellular vesicles (EVs). EVs were isolated and characterized, followed by analysis of the small RNAs and proteins encapsulated within them using small RNA sequencing and proteomics, respectively.Results: Our results revealed that cucurbitacin IIa alleviated colitis symptoms in DSS-treated rats, along with changes in the morphology and composition of intestinal EVs. Notably, EVs from cucurbitacin IIa-treated rats also mitigated colitis symptoms in DSS-treated rats. Further analysis showed that cucurbitacin IIa modified the protein profiles and microRNA composition of EVs extracted from the feces of colitis rats. Specifically, microRNA-30b-5p, significantly increased by cucurbitacin IIa, was found to alleviate colitis symptoms in DSS-treated rats. In conclusion, cucurbitacin IIa appears to alleviate colitis by promoting the release of microRNA-30b-5p from host-derived extracellular vesicles.Conclusion: These findings enhance our understanding of cucurbitacin IIa’s effects on intestinal health and offer potential new therapeutic targets for inflammatory bowel disease treatment.Keywords: colitis, cucurbitacins, extracellular vesicles, inflammation, microRNA